A Genomic Perspective Across Earth’s Microbiomes Reveals That Genome Size in Archaea and Bacteria Is Linked to Ecosystem Type and Trophic Strategy - Rodríguez-Gijón, Alejandro; Nuy, Julia K.; Mehrshad, Maliheh; Buck, Moritz; Schulz, Frederik; Woyke, Tanja; Garcia, Sarahi L. (Frontiers in Microbiology, 2022)
Our view of genome size in Archaea and Bacteria has remained skewed with data dominated by genomes of microorganisms cultivated under laboratory settings. However, the continuous effort to catalog Earth’s microbiome provides an opportunity to revise our perspective on genome size distribution. We present a meta-analysis that includes 26 101 representative genomes from 3 published databases; metagenomic assembled genomes (MAGs) from GEMs and stratfreshDB, and isolates from GTDB. Aquatic and host-associated microbial genomes present on average the smallest estimated genome sizes (3.1 Mbp and 3.0 Mbp respectively). These are followed by terrestrial microbial genomes (average 3.7 Mbp), and genomes from isolated microorganisms (average 4.3 Mbp). On the one hand, aquatic and host-associated ecosystems present smaller genomes sizes in genera of phyla with genome sizes above 3Mbp. On the other hand, estimated genome size in phyla with genomes under 3 Mbp showed no difference between ecosystems. Moreover, we observed that when using 95% average nucleotide identity (ANI) as an estimator for genetic units, only 3% of MAGs cluster together with genomes from isolated microorganisms. Although there are potential methodological limitations using MAGs, we found that in genome clusters containing both environmental MAGs and isolate genomes, MAGs were estimated only an average 3.7% smaller than isolate genomes. In summary, despite biases, the estimated genome size of MAGs offers valuable insights. Finally, to better understand the ecological drivers of genome size, we discuss the known and the overlooked factors that influence genome size in different ecosystems, phylogenetic groups, and trophic strategies.